The Development of Pragmatic-Based English Learning Material for Front Office - Kadek Feni Aryati; Made Budiarsa; I Made Suastra; Anak Agung Putu Putra (ITScience (Information Technology and Science), 2022)
This study aimed at (1) describing the realization of the use of teaching materials in learning English speaking skills in the field of front office services, (2) developing learning materials for English speaking skills in the field of front office services, and (3) examining the effectiveness the learning materials for English speaking skills in the field of front office services with a pragmatic approach. This research was conducted using Research and Development (R&D) research methods and applying Borg and Gall (1983). Based on the results of the analysis, it was found that learning English for tourism and hospitality currently does not include linguistic elements in it. The books or modules available were limited. Based on this reality, this research develops two educational products, namely a pragmatic-based syllabus and module. The syllabus and modules have 12 learning topics that have been adapted to the use of English for hotel front office services. Learning materials for English speaking skills for front office services with a pragmatic approach are effective for use in organizing the teaching and learning process as evidenced by the t-test results, namely 0.001 (0.001 <0.005). In addition, the perceptions of students and lecturers also showed a positive response to the modules developed in this study.